Vegetable oil in Ecuador: a profitable sector with market power? - Espinoza, Erika (2024)
Within Industrial Organization, the SCP paradigm is crucial for understanding the situation of companies and sectors, and it is essential to apply it in industries of staple products to counteract the adverse effects of concentrated markets. Therefore, the present research aims to analyze the relationship between market structure, behaviour, and performance according to the SCP paradigm in the vegetable oil sector in Ecuador during the period 2014-2021. The data were processed using descriptive statistics, correlational analysis, and explanatory studies. Within the framework of the SCP paradigm, the market structure was calculated using the Herfindahl-Hirschman Index, the behaviour of firms was determined by examining how they manage the market using prices as an indicator of market power, and the outcomes of the oligopoly were measured using profitability ratios such as ROA and ROE. The results indicate that the vegetable oil sector belongs to an oligopolistic market. This structure grants firms market power, enabling them to set prices, achieve higher profits, and increase profitability, resulting in better performance.